2018
DOI: 10.1017/ice.2018.144
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of ultraviolet light intensity on disinfection performance through the use of ultraviolet measurements and simulation

Abstract: We measured the disinfection of MRSA and Clostridium difficile spores using an ultraviolet C (UV-C) device, and we correlated those results to measurements and computer simulations of UV-C surface intensity. The results demonstrate both large differences in UV light intensity across various surfaces and how this leads to significant differences in disinfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Our findings are consistent with 3 recent reports in demonstrating that measurements of irradiance may be useful in understanding decontamination performance of different devices. [20][21][22] If a radiometer is available, measurement of irradiance can be completed quickly and easily. Alternatively, commercial test cards can provide a simple and easy-to-use colorimetric assessment of UV output.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with 3 recent reports in demonstrating that measurements of irradiance may be useful in understanding decontamination performance of different devices. [20][21][22] If a radiometer is available, measurement of irradiance can be completed quickly and easily. Alternatively, commercial test cards can provide a simple and easy-to-use colorimetric assessment of UV output.…”
Section: Discussionmentioning
confidence: 99%
“…Variables that affect the amount of UV delivered to surfaces and the resulting log 10 reductions of pathogens achieved include the amount of irradiance generated by the UV lamp(s), the distance from the lamp to the exposed surface, the angle at which the UV strikes the surface, and whether the surface is in direct line of sight of the lamp or receives light that has been reflected off other objects (ie, surfaces in shaded areas). 7,12,17,23 The intensity of UV irradiance is inversely proportional to the square of the distance between the lamp and the exposed surface, based on the "inverse square law." 28 Therefore, the UV intensity received by a surface decreases exponentially the further the surface is from the lamp.…”
Section: Basics Of Uv Lightmentioning
confidence: 99%
“…Irradiance levels of ∼1,000 uW/cm 2 were achieved on vertical surfaces located in the direct line of sight of the device at distances in the range of 1.3 m (4 feet), whereas irradiance of only 3-10 uW/cm 2 were achieved on horizontal surfaces located in shaded areas at distances in the range of 3.3 m (10 feet) from the device. 12,22,23 Despite the marked dropoff in UV-C dose in shaded areas, 2 log 10 reductions were achieved for MRSA at both 1.3 and 3.3 m. In contrast, C. difficile spores are relatively resistant to UV-C. Minimal reductions in C. difficile spores were achieved in shaded areas, and both distance and orientation of the carriers had a more marked impact on the efficacy of UV-C. Tande et al 23 reported similar findings for the UV-C doses delivered to various locations in a room, and other studies have also demonstrated that UV-C doses are lowest when the surface is not in the direct line of sight of the lamp.…”
Section: Basics Of Uv Lightmentioning
confidence: 99%
See 2 more Smart Citations